Community development and civil society making connections in the European context - Henderson, Paul 1942-; Vercseg, Ilona 1945- (Policy, 2010)
Set within the context of Europe, this book demonstrates the contribution that community development can make to strengthening civil society. The book interweaves case studies with discussion of community development principles and theory to provide a critical and accessible approach
Title from publisher's bibliographic system (viewed on 02 Sep 2022)
Keywords: Community development / Great Britain; Civil society / Great Britain; Zivilgesellschaft; Gemeinwesenarbeit; Großbritannien